Positive Discipline in Schools: Educating for Life (Journal of Parents and Teachers, 2023)
Positive Discipline is an educational style based on encouragement, mutual respect, kindness and firmness, and the development of socio-emotional skills that can be used in any formal and non-formal educational space with children, adolescents, and young people. To implement this model in a school, the commitment of the management team is essential, involving the entire educational community and generating a plan with phases that are affordable to the starting reality.It is a process that requires effort and dedication, now, with perseverance, coexistence is improved and a good integral development of all the people belonging to that center is achieved.
Keywords: positive discipline; classroom; learning beliefs; encouragement; educating for life; social-emotional skills; school; students; educational style